P202 Quantum blue anti-infliximab: development and evaluation of a point of care rapid test for measuring anti-infliximab antibodies in human serum. (25th January 2019) - Bantleon, F; Schneider, M; Ricken, B; Velayutham, S; Trapani, D; Afonso, J; Magro, F; Abel, A
Abstract: Background: The treatment of patients suffering from an inflammatory disease, like inflammatory bowel disease (IBD) may involve biologicals like infliximab. However, infliximab is a chimeric human/murine monoclonal antibody and can induce a significant immune response. Within this immune response different anti-infliximab antibodies are formed, belonging to different isotypes (eg, IgM, IgG1, IgG4, and IgE) with different specificities and affinities. The detection of these anti-infliximab antibodies is crucial to adjust the therapy with infliximab or to justify a switch of the used drug. For the fast and easy detection of the anti-infliximab response a lateral flow test was developed and preliminary evaluated. Methods: A drug-sensitive bridging lateral flow test was developed using infliximab-fragment coated gold nanoparticles and membrane immobilised infliximab to detect polyclonal anti-infliximab antibodies in a diluted human serum sample. Standardisation is based on a specific monoclonal anti-infliximab antibody. Using this approach limit of detection (LoD) and limit of quantification (LoQ) were determined according to CLSI EP17-A2 guideline. The influence of rheumatoid factors as well as various blood conditions was evaluated. Patient samples were used to compare the Quantum Blue ® Anti-Infliximab rapid test with a commercially available ELISA test. These results were used to establish a ROC curve analysis and to identify a clinical relevant cut-off value. Results: The current Quantum Blue ® Anti-Infliximab test allows the analysis of diluted human serum samples within 15 min. The samples are diluted in chase buffer (1:10) before application on the test cassette. The readout is performed with a Quantum Blue ® Reader resulting in a measuring range of 0.5 to 12 μg/ml. Due to missing international standard material and the polyclonal immune response in patients, the Quantum Blue ® Anti-Infliximab was classified as semi-quantitative. The test exhibits a LoD of 0.31 μg/ml and a LoQ of 0.5 μg/ml. Rheumatoid factors as well as various blood conditions showed no interference to test results. A clinical cut-off value of 1.44 μg/ml results in a sensitivity of 0.86 and a specificity of 0.94 obtained by ROC curve analysis with 78 patient samples. Conclusions: The here presented Quantum Blue ® Anti-Infliximab test allows the fast and easy detection of anti-infliximab antibodies in human serum within 15 min. The assay can be carried out with a minimum of external equipment and may therefore support a fast adaption of the treatment regime, providing a valuable tool for pro-active therapeutic drug monitoring.